Study of Ground Vibration Reduction Using Fault Tree Analysis Method on Blasting Activity in PT. Semen Baturaja Persero, Tbk. - Jihan F. Lubis; Taufik Toha; Ngudiantoro Ngudiantoro (Program Pascasarjana Universitas Sriwijaya, 2018)
Abstract Limestone mining activities at PT. Semen Baturaja Persero, Tbk use blasting activity that produces ground vibrations. Based on the measurement result on vibration level, the maximum value for vibration is 4.66 mm/s. The results of the data show that the level of emission has exceeded the standard limits for second class buildings (3 mm/s) based on (SNI) 7571: 2010 while the blasting activity is only 175-300 m from the nearest settlement. Fault Tree Analysis is used to analyze undesired events in a system or work set. Reconstruction of Fault Tree Analysis with Boolean algebra yields 5 event combinations that have the highest chance of generating ground vibrations. The event with the highest failure rate is X11 (the number of bursting holes simultaneously) with failure rate of 0.813 and X12 (fast timing delay) with failure rate (0.750). The USBM formulation obtained 3 mm/s vibration results when the number of bursting holes was reduced from 5 holes to 2 holes/delays with a quantity of 43 kg/delay. Based on Shotplus simulation, the company is advised to replace the blasting delay system from electricity to electronics to produce minimal explosion of ground vibration so as not to damage the environment.Keywords: Blasting, flyrock, Vibration, powder factor Abstrak (Indonesian) Proses peledakan batu kapur di PT. Semen Baturaja Persero, Tbk, menghasilkan efek peledakan berupa getaran tanah. Berdasarkan hasil pengukuran terhadap tingkat getaran didapatkan nilai maksimum untuk getaran sebesar 4.66 mm/s. Hasil data menunjukkan tingkat geraran telah melebihi batas standar untuk bangunan kelas dua 3 mm/s (SNI) 7571:2010, sementara kegiatan peledakan hanya berjarak 175-300 m dari pemukiman terdekat. Fault Tree Analysis digunakan untuk menganalisis kejadian (undesired event) yang tidak diinginkan dalam sebuah sistem atau rangkaian pekerjaan. Rekonstruksi Fault Tree Analysis dengan analisis aljabar Boolean menghasilkan 5 kombinasi event yang memiliki peluang tertinggi untuk menghasilkan getaran tanah. Event dengan tingkat kegagalan tinggi adalah event X11(jumlah lubang meledak bersamaan) dengan laju kegagalan 0.813 dan X12 (delay timing cepat) dengan laju kegagalan (0.750). Formulasi USBM memperoleh hasil getaran 3 mm/s apabila jumlah lubang yang meledak bersamaan direduksi dari 5 lubang menjadi 2 lubang perdelay dengan kuantitas 43 kg/delay. Berdasarkan simulasi softwate shotplus perusahaan disarankan untuk mengganti sistem delay peledakan dari listrik menjadi elektronik untuk menghasilkan peledakan yang minim getaran tanah sehingga tidak merusak lingkungan.